Internetworking with TCP/IP - Comer, Douglas (Upper Saddle River, N.J. : Prentice Hall, 2000)
A detailed explanation of how physical networks are connected into internets; and an introduction to Internet addressing, routing, subnets, and supernets. Next, understand UDP and TCP; key routing protocols such as RIP and OSPF; Internet multicasting with IGMP; and more. Comer explains client-server interaction and socket interfaces; DNS and DHCP; and key Internet applications such as FTP, NFS, MIME, SMTP, and SNMP. You'll find a detailed introduction to Internet security, firewall design, and VPNs - and even an insightful preview of tomorrow's IPng and IPv6 protocols.
Includes bibliographical references (v. 1, p. [721]-722) and index.
oif 17/02/15
Loan
Keywords: Internetworking (Telecommunication); TCP/IP (Computer network protocol); Client/server computing; principles,protocols and architecture